Olanzapine Loaded Nanostructured Lipid Carriers via High Shear Homogenization and Ultrasonication - Adejumoke Lara Ajiboye; Uttom Nandi; Martin Galli; Vivek Trivedi (MDPI AG, 2021)
The aim of this study was to understand the effect of high shear homogenization (HSH) and ultrasonication (US) on the physicochemical properties of blank and olanzapine loaded nanostructured lipid carriers (NLCs) along with their drug loading potential and drug release profiles from formulated particles. NLCs were prepared with different ratios of Compritol and Miglyol as the solid and liquid lipids, respectively, under changing HSH and US times between 0 to 15 min. The surfactants (Poloxamer 188 (P188) and tween 80) and the drug content was kept constant in all formulations. The prepared NLCs were evaluated for particle size, polydispersity index, zeta potential, drug crystallinity and chemical interactions between lipids and OLZ. The in-vitro drug release was performed using dialysis tube method in phosphate buffer solution (PBS) at pH 7.4. The formulated NLCs were negatively charged, spherically shaped and monodisperse, with particle sizes ranging from 112 to 191 nm. There was a significant influence of US time on the preparation of NLCs in comparison to HSH, where a significant reduction in the mean particle diameter was seen after 5 min of sonication. An increase of Miglyol content in NLCs led to an increase in particle size. In general, application of US led to decrease in particle size after HSH but an increase in particle diameter of low Miglyol containing preparation was also observed with longer sonication time. OLZ was successfully encapsulated in the NLCs and a total release of 89% was achieved in 24 h in PBS at pH 7.4.